Dynamic Inconsistency in Risky Choice: Evidence from the Lab and Field - Heimer, Rawley; Iliewa, Zwetelina; Imas, Alex; Weber, Martin (American Economic Review, 2025)
We document a robust dynamic inconsistency in risky choice. Using a unique brokerage dataset and a series of experiments, we compare people's initial risk-taking plans to their subsequent decisions. Across settings, people accept risk as part of a loss-exit strategy—planning to continue taking risk after gains and stopping after losses. Actual behavior deviates from initial strategies by cutting gains early and chasing losses. More people accept risk when offered a commitment to their initial strategy. Our results help reconcile seemingly contradictory findings on risk-taking in static versus dynamic contexts. We explore implications for theory and welfare. (JEL D81, G13, G24, G41)